Monte carlo investigation of defect-driven ferroelectric phase-transition in two dimensional defected film - S. Srinoi (2018)
In this work, the hysteresis loops of ferroelectric film with defects were investigated with Monte Carlo simulation and the modified Heisenberg model (discrete vector model) with DIFFOUR type interaction. The effect of localized vacancy defects on the electrical properties of ferroelectric film was studied. The defected ferroelectric film was simulated on the two-dimensional lattice with periodic boundary conditions. From results, at a given electric field, the hysteresis loop area was found to depend on the defect concentration of system. The higher defect concentration, the smaller hysteresis loop was obtained, which resulted from weaker ferroelectric interaction. © 2014 Taylor & Francis Group, LLC.